2015
DOI: 10.14260/jemds/2015/497
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Hip Dislocation in Children Younger Than 3 Years : A Series of 3 Cases

Abstract: ABSTRACT:The musculoskeletal anatomy of children is quite different from that of adults. The capsule, periosteum and other soft tissues surrounding the joints is very pliable and dislocations can occur even following trivial injuries. However dislocation occurring in a child population is a rare entity. There are a few case reports of hip dislocations in children < 3 years. We present here a series of 3 cases of paediatric hip dislocations which presented to us for management. The age of the children were betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Posterior dislocation of the hip joint due to trauma in children is can cause many complications .the incidence of different complications is as follows: Nerve injuries in 5% 2,9 Avascular necrosis in 8% to 10%, Chondrolysis reported in 6% of the children. Follow up of all the three cases was uneventful and produced good long-term results when compared with adults 10 .…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Posterior dislocation of the hip joint due to trauma in children is can cause many complications .the incidence of different complications is as follows: Nerve injuries in 5% 2,9 Avascular necrosis in 8% to 10%, Chondrolysis reported in 6% of the children. Follow up of all the three cases was uneventful and produced good long-term results when compared with adults 10 .…”
Section: Discussionmentioning
confidence: 76%
“…Dislocation of the hip joint in children who are younger than 16 years is extremely uncommon 2 , (0.8 cases per million/year) and around 80% of these present as posterior dislocations 2,9,10,11 . It is more common in boys (4:1) 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further did a detailed search of the literature for traumatic pediatric hip dislocations in the Asian population, and we came across only two studies which had reported the entity ( Table 1 ) [ 5 , 6 ].…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%